Molecular Surveillance for Potential Zoonotic Pathogens in Troglophilus Bats: Detection and Molecular Characterization of Bat Coronaviruses in Southern Italy - Francesco Mira; Francesca Gucciardi; Giorgia Schiró; Rosario Grasso; Maria Teresa Spena; Gábor Kemenesi; Claudia Vaiana; Davide Anzá; Laura Di Paola; Santina Di Bella; Annalisa Guercio; Giuseppa Purpari (Pathogens)
The recent COVID-19 pandemic has renewed interest in bats, as they are natural hosts for numerous viruses, some of which have crossed species boundaries. Despite continued efforts in the past, the ecology of bat-related viruses in a significant part of national territories, such as Italy, remains largely unexplored. Herein, we describe the detection and molecular characterization of bat coronaviruses, identified during a viral survey on selected potential zoonotic pathogens (lyssavirus and coronaviruses) carried out in Sicily, southern Italy. A total number of 330 samples were collected from 149 bats in a period (November 2020–April 2023) overlapping the COVID-19 pandemic. All samples tested negative for lyssavirus and SARS-CoV-2, while 12 bats (8.05%) tested positive to a pan-coronavirus assay. Both alphacoronaviruses and betacoronaviruses were identified in samples from three species (Miniopterus schreibersii, Rhinolophus ferrumequinum, and Rhinolophus hipposideros). Strain sequences were related to coronaviruses detected in the last decade in northern Italy as well as in other countries bordering the Mediterranean basin, suggesting a widespread diffusion of these strains. This study supports the need for further monitoring efforts and early detection of circulating coronavirus genotypes, particularly for those which have been repeatedly emerging as zoonotic spillovers.